Learning by heart - Barth, Roland S. (Jossey-Bass education series., 2001)
A decade after publication of his best-selling book, Barth returns to the schoolhouse. Drawing from a career committed to building schools rich in community, learning, and leadership, he shows how to accomplish the most difficult task of school reform - transforming a school's culture so that it will be hospitable to human learning. In an engaging conversational style, he suggests how school people can become the architects, engineers, and designers of their own schools - and of their own destinies.